The mass–size relation of luminous red galaxies from BOSS and DECaLS. Issue 1 (20th July 2018) - Favole, Ginevra; Montero-Dorta, Antonio D; Prada, Francisco; Rodríguez-Torres, Sergio A; Schlegel, David J
ABSTRACT: We use the DECaLS DR3 survey photometry matched to the SDSS-III/BOSS DR12 spectroscopic catalogue to investigate the morphology and stellar mass–size relation of luminous red galaxies within the CMASS and LOWZ galaxy samples in the redshift range 0.2 < $z$ < 0.7. The large majority of both samples is composed of early-type galaxies with De Vaucouleurs profiles, while only less than 20 per cent are late-type exponentials. We calibrate DECaLS effective radii using the higher-resolution CFHT/MegaCam observations and optimize the correction for each morphological type. By cross-matching the photometric properties of the early-type population with the Portsmouth stellar mass catalogue, we are able to explore the high-mass end of the distribution using a large sample of 322994 galaxies over 4380 deg 2 . We find a clear correlation between the sizes and stellar masses of these galaxies, which appears flatter than previous estimates at lower masses. The sizes of these early-type galaxies do not exhibit significant evolution within the BOSS redshift range, but a slightly declining redshift trend is found when these results are combined with $z$ ∼ 0.1 SDSS measurements at the high-mass end. The synergy between BOSS and DECaLS has important applications in other fields, including galaxy clustering and weak lensing.